(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
This article explores adjectives that describe non-physical characteristics of a person in contemporary Russian. The research identifies five major semantic groups of such adjectives: characterological, intellectual, emotional, moral-ethical, and socio communicative. The functional and pragmatic features of these lexical units are analyzed, with particular attention to sociocultural and media-related influences on their usage and development. The article also examines trends in lexical innovation, including borrowings and neologisms, which reflect the dynamic processes of language renewal.